Biopsy Gleason score and the duration of testosterone suppression among men treated with external beam radiation and 6 months of combined androgen blockade - Martin, Neil E.; Chen, Ming‐Hui; Nguyen, Paul L.; Beard, Clair J.; Loffredo, Marian J.; Kantoff, Philip W.; D'Amico, Anthony V. (BJU international, 2012)
Study Type – Therapy (case series) Level of Evidence 4 What's known on the subject? and What does the study add? The return of testosterone to normal levels following short‐course androgen blockade in prostate cancer is variable. Factors associated with a longer time to recovery include older age and lower baseline testosterone level. In this study, we found that among men treated with 6 months of combined androgen blockade and radiation therapy, higher biopsy Gleason grade was associated with a shorter time to testosterone normalization. OBJECTIVE • To determine whether the biopsy Gleason score is associated with duration of testosterone suppression following 6 months of combined androgen blockade (CAB) and radiation therapy (RT) in men with prostate cancer (PCa). PATIENTS AND METHODS • The study cohort consisted of 221 men with PCa treated with RT and 6 months of CAB between 1996 and 2005. • We defined the duration of testosterone suppression as the time between the last day of CAB and the date the testosterone returned to ≥252 ng/dL. We used Cox regression multivariable analysis to relate biopsy Gleason score to duration of testosterone suppression following cessation of CAB. RESULTS • A biopsy Gleason score of 8–10 had an adjusted hazard ratio (AHR) of 1.56 (95% confidence interval [CI] 1.04, 2.34; P= 0.03) for a shorter time to testosterone normalization relative to Gleason 6. Specifically, the 51 men with biopsy Gleason score of 8–10 had a median time to testosterone normalization of 17.0 months compared with 22.1 months and 23.8 months for those with biopsy Gleason ≤6 and 7, respectively. • Increasing age was significantly associated with a longer duration of testosterone suppression (AHR of 0.95 [95% CI 0.92, 0.97; P < 0.001]) as was a higher baseline PSA (AHR 0.82 [95% CI 0.69, 0.97; P= 0.02]). CONCLUSION • A biopsy Gleason score of 8–10 was associated with a shorter period of testosterone suppression following 6 months of CAB and RT. These data are consistent with the hypothesis that a factor released from high‐grade PCa cells may impact on testosterone production.